A Consistency and An Inconsistency of The Leviticus Translator - Philip Suciadi Chia (Theological Journal Kerugma, 2019)
This paper has a few goals. First is to discover if the Greek translator of Leviticus uses literal (consistent) and / or free (inconsistent) translation technique. Then, this paper will list and group the evidences of the consistency of the Greek translator in this book. If there are any examples that show the inconsistency to the MT or looseness of the translator, then this paper will study every example carefully and it will categorize into a group. This group will be created based on the examples that share the same pattern or the similarities. The comparison of MT and LXX will be used as the methodology of this paper. Every verse will be analyzed and presented in comparison format until chapter five to have a basic knowledge of the patterns and the characteristics of the Greek Translator. The patterns, however, will be scrutinized in the whole book of Leviticus. In depth and a detailed analysis of this comparison will be put on the appendices. This methodology will be employed to accomplish the goals of this paper.